Equal Despite Different Entitlements? M.C. Piepers’ Ambiguous Conceptualization of Legal Equality (1898) - Linde, Otto; Legene, Susan (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
In ‘Gelijkstelling van Vreemde Oosterlingen met Europeanen’ (‘Legal Equation of Foreign Asians with Europeans’), published in 1898 in Tijdschrift voor Nederlandsch-Indië, the liberal intellectual M.C. Piepers argued against the legal equation of the resident Japanese subjects in the Netherlands Indies with the Europeans. To make such equation happen, Parliament in the Netherlands discussed a change in the Law in order to alter the provisions with respect to the binary colonial distinction between Europeans and all other people in the Netherlands Indies as laid down in article 109 of the ‘colonial constitution’ (‘regeringsreglement’) of 1854. The change was needed for the 1896/1897 trade-agreement between the Netherlandic Empire and Imperial Japan to be implemented. Piepers warned against this ‘surrender’ to Japanese claims, arguing that the change emerged from a wide-spread misunderstanding of the legal and constitutional regulations with respect to legal entitlements in the Netherlands Indies. This article interprets Piepers’ passionate defense of the judicial status quo concerning equality founded on ‘legal’ definitions of difference, as an avant la lettre constitutional ‘apartheid’ argument. Piepers’ view on Netherlands Indies state formation started from a legal pluralism with subjectively defined groups. We will argue how in these subjectivities resonate three levels of power relations around 1900: a) geopolitical; b) national/state/colonial c) individual; with long-living aftermaths. Piepers final line of defending the status quo is the distinction between the just de jure equality in colonial society and the unjustified de facto hierarchical relationships between the different population groups. This very opposition between just laws and unfair practices in colonial governance obscures how the Eurocentrism of European (liberal) legal thought inevitably resulted in racist practice